2022
DOI: 10.1097/md.0000000000030358
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of semi-customized exercises in preventing low back pain in high school volleyball players: A randomized controlled trial

Abstract: Background: Low back pain (LBP) is a common injury in high school volleyball players. We hypothesized that a prevention program could decrease the incidence of LBP in high school volleyball players. This study was an in-season cluster-randomized controlled trial.Methods: We block-randomized 8 high school volleyball teams comprising 70 players aged 15 to 17 years into the intervention (4 teams, 34 players) and control (4 teams, 36 players) groups. The intervention program consisted of 9 physical function tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
1
0
4
Order By: Relevance
“…Com impacto não restrito à dor lombar inespecífica, os isquiotibiais tensos são fatores preditivos negativos na união óssea na espondilólise lombar, afetando também as lombalgias que comprometem a extensão (MIZOGUCHI et al, 2022).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Com impacto não restrito à dor lombar inespecífica, os isquiotibiais tensos são fatores preditivos negativos na união óssea na espondilólise lombar, afetando também as lombalgias que comprometem a extensão (MIZOGUCHI et al, 2022).…”
Section: Resultsunclassified
“…O aumento da tensão lombar devido à tensão nos isquiotibiais foi observada em jogadores de voleibol, em decorrência da necessidade de maior flexão do quadril, levando a uma lombalgia decorrente da flexão (MIZOGUCHI et al, 2022). Essa tensão é um dos principais problemas encontrados em atletas com lombalgia (HUANG et al, 2020).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A previous clinical trial of adults with chronic low back pain found that interventions designed to improve thoracic flexibility, such as mobilization or manipulation positively influenced lumbar mobility, which resulted in an improvement in disability and mental state in people with low back pain [27]. Another clinical trial involving 70 volleyball players, aged between 15 and 17, from high schools showed that participants assigned to the intervention group where they engaged in preventative exercises designed to improve thoracic dynamic mobility and stabilization had a significantly lower incidence of low back pain in the follow-up period of 4 weeks [28]. Therefore, reduced thoracic flexibility observed in the present study could be a contributing factor to low back pain in individuals with achondroplasia.…”
Section: Discussionmentioning
confidence: 99%